Diamond Smugglers - Fleming, Ian (Macmillan Company New York, 1957)
Aided by an ex-MI5 agent and International Diamond Security Organization operative going by the alias (3z(BJohn Blaize,(3y (BFleming chronicled the IDSO$1 (Bs infiltration of the (3z(Bmillion-carat network(3y$1 (Bthe world$1 (Bs most notorious diamond smuggling ring. Every year, a shadowy band of racketeers pirated a fortune in diamonds out of Africa, and the majority of the stolen gems wound up in the hands of Communist nations. In response, the IDSO commissioned a private army, led by legendary British spymaster Sir Percy Sillitoe, to penetrate and topple the ring. And when the operation was complete, the Sunday Times gave the story to Fleming, who had impressed Sillitoe with his 1956 Bond adventure Diamonds Are Forever.s
Keywords: Espionage True Accounts; Political Intelligence; Author Biographies; Diamants Contrebande; Diamond smuggling